2020
DOI: 10.3390/ijerph17186703
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Practices on Water, Sanitation, and Hygiene from a Fishing Community along Lake Malombe, Southern Malawi

Abstract: People living in fishing communities have a high burden of preventable water, sanitation, and hygiene (WASH) related diseases but have often been neglected in research and policy. We explored practices and perspectives on WASH among fishing villages around Lake Malombe, Malawi. We employed a mixed methods design, and data were initially collected through participant observations (five weeks), followed by a second phase of qualitative interviews (n = 16), focus group discussions (n = 7), and quantitative survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…For river fishing, huts are built in the vicinity of the place where the traps are to be set, for the fishers live there for as long as the season lasts. ' (p. 142) Similar to our study, Kalumbi et al (2020) also found gaps in water, sanitation, and hygiene access within fishing communities; but variations in handwashing access especially may be attributed to the culture of fishing communities in the Tonga and Ngonde ethnic group in our study compared with the Yao ethnic group in the Kalumbi et al (2020) study.…”
Section: Culture Of Fishers and Their Communitiessupporting
confidence: 86%
See 2 more Smart Citations
“…For river fishing, huts are built in the vicinity of the place where the traps are to be set, for the fishers live there for as long as the season lasts. ' (p. 142) Similar to our study, Kalumbi et al (2020) also found gaps in water, sanitation, and hygiene access within fishing communities; but variations in handwashing access especially may be attributed to the culture of fishing communities in the Tonga and Ngonde ethnic group in our study compared with the Yao ethnic group in the Kalumbi et al (2020) study.…”
Section: Culture Of Fishers and Their Communitiessupporting
confidence: 86%
“…Despite the wealth indicators, other studies have shown that the willingness to pay (cash) for a low-cost pit latrine remains low in shoreline communities (Holm et al, 2016). Pit latrine sharing was commonly reported by both our study respondents along Lake Malawi and by Kalumbi et al (2020) for communities along Lake Malombe.…”
Section: Economicscontrasting
confidence: 48%
See 1 more Smart Citation
“…The majority of the Lake Malombe local population depends on unprotected water from the lake (Kalumbi et al 2020). In the upper catchment of the lake, water from rivers that drain into the lake is heavily contaminated with agricultural chemicals such as inorganic fertilizers, insecticides, and other human contaminants although studies focusing on the limnological status of these rivers are scarcely available.…”
Section: Resultsmentioning
confidence: 99%
“…Kalumbi et al [ 1 ] have highlighted the growing threats to aquatic resources and public health from environmental degradation caused principally by improper waste disposal practices in Africa and other parts of the world. The threats are incompatible not only with the SDG 6 on sanitation and hygiene but also with SDG 14, which emphasises the conservation and sustainable use of the oceans, seas, and marine resources.…”
Section: Introductionmentioning
confidence: 99%